ANALISIS VEGETASI DAN DEGRADASI JENIS TUMBUHAN HUT AN GAMBUT SETELAH KEBAKARAN DIKAWASAN TAMAN NASIONAL TANJUNG PUTING KALIMANTAN TENGAH - Yusuf, Razali (Research Center for Biology-Indonesian Institute of Sciences, 2000)
This report deals with the result of an ecological study with reference to disclose the effect of wild fire and human interference on the peat forest deterioration and plant species degradation in Tanjung Harapan Camp, Tanjung Putting National Park, Central Kalimantan. By using quadrate method, a one-hectare both fired and unfired (natural) plots were compared.Within the fired-plots, only 19 plant species were recorded belongs to 16 genera and 12 families, while in the unfired plots, 50 plant species belongs to 34 genera and 23 families were found. The dominant species in both plots was component of pioneering species;Macaranga hypoleuca was one of the dominant.The result of successions after one year of fire showed that Dillenia suffruticosa and Baccaurea bracteata became the most frequent species found with the largest area of distribution.